Expansion of South African Xitsonga terminology through importing from agrarian pursuits of Xitsonga linguistic communities in Mozambique and Zimbabwe - Mabunda, Godfrey Machisana (My University, 2023)
This research report delves into the redundancy of the agrarian terminology in South African Xitsonga. Agrarianism signifies farming and spirituality in a rural setting. As the mainstay of Vatsonga culture, the agricultural lifestyle boasts a host of terminology attached to it. There is an overt need for agrarian terminology in the South African Xitsonga today to enhance its lexicon. This study posits that the erosion of agrarian terminology in the South African Xitsonga can be linked to the disruption of native farming by colonial powers and the far-reaching effects that Christianity had on Vatsonga faith, which had exisited since antiquity. The intellectualisation of Xitsonga also facilitated the eschewing and eventual loss of the longstanding agricultural elements of the language. The Xitsonga linguistic communities in Mozambique and Zimbabwe still use some of the agrarian terminology that could serve to aid the expansion of South African Xitsonga.
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Arts in Translation to the Faculty of Humanities, University of the Witwatersrand, 2023
Keywords: South African Xitsonga; Linguistic communities; Agrarian terminology